2020
DOI: 10.3390/catal10030269
|View full text |Cite
|
Sign up to set email alerts
|

Selectivity and Sustainability of Electroenzymatic Process for Glucose Conversion to Gluconic Acid

Abstract: Electroenzymatic processes are interesting solutions for the development of new processes based on renewable feedstocks, renewable energies, and green catalysts. High-selectivity and sustainability of these processes are usually assumed. In this contribution, these two aspects were studied in more detail. In a membrane-less electroenzymatic reactor, 97% product selectivity at 80% glucose conversion to gluconic acid was determined. With the help of nuclear magnetic resonance spectroscopy, two main side products… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 50 publications
(72 reference statements)
0
9
0
Order By: Relevance
“…With the help of nuclear magnetic resonance (NMR) spectroscopy, a product selectivity of 97 % was reported. Additionally, glucose conversion of 80 % and E‐factor of 9 were obtained [22] . A further distinctive result of the application of an electroenzymatic process was reported by Sokol et al.…”
Section: Examples Of Electroenzymatic Processesmentioning
confidence: 57%
See 2 more Smart Citations
“…With the help of nuclear magnetic resonance (NMR) spectroscopy, a product selectivity of 97 % was reported. Additionally, glucose conversion of 80 % and E‐factor of 9 were obtained [22] . A further distinctive result of the application of an electroenzymatic process was reported by Sokol et al.…”
Section: Examples Of Electroenzymatic Processesmentioning
confidence: 57%
“…The amount of waste is difficult to quantify, we recommend excluding water and normalize the waste generation to the reactor volume [21,22] …”
Section: Overview Of Important Performance Indicatorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Computational methods such as design of experiments (Tosstorff et al, 2017) or modelling in combination with simulations (Bormann et al, 2021) appear to be particularly useful for an accelerated implementation of electroenzymatic processes in industry. Furthermore, sustainability of the electroenzymatic process should be evaluated (Varničić, 2020).…”
Section: Combining the Advantages Of Enzyme Catalysis And Electrochem...mentioning
confidence: 99%
“…Therefore, the need to analyze the product resulting in the reaction at the EBFC electrode is needed. Varničić et al [84] produced membrane-less EBFCs and used nuclear magnetic resonance spectroscopy to determine the production of two main products: D-arabinose and formic acid. The authors found that the production of this product was influenced by the enzyme selection on the cathode side of EBFC.…”
Section: System In Ebfcmentioning
confidence: 99%